BIMBINGAN KELOMPOK UNTUK PESERTA DIDIK YANG MEMILIKI KEPERCAYAAN DIRI RENDAH DI SMP UMMUL QURO - Hafsah Nurrobi; Heris Hendriana; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Self-confidence is a very important capital for a person to have the choice to be aware of themselves. Confidence is one of the side effects of positive self-realization, by having the confidence of students who are ready to cultivate the abilities, interests and possibilities that exist in him so that it can be formed into victory or around it is called achievement.. This research was conducted using a qualitative descriptive approach. The purpose in this study is to explain the implementation of group guidance for learners who have low self-confidence in Ummul Quro Junior High School.The subjects of this study were 6 learners (3 men and 3 women) Class VIII at Ummul Quro Junior High School. The information obtained in this review is information obtained through interviews, observations and documentation. It can be concluded that the number of directions for learners who have low self-confidence is very attractive in managing low self-confidence in school.Keywords: Group guidance, self confidence